The Challenge for the Central American Integration System (SICA): The Withdrawal of Costa Rica During the Cuban Migrant Crisis 2015 - Stein, Damaris (UI Scholars Hub, 2020)
Central America has the longest experience with regional integration efforts apart from Europe and regional integration was on its rise with the establishment of the Central American Integration System (SICA). However, the organization has been struggling to move the integration process further; experiencing a climax of fragmentation when Costa Rica left SICA during the Cuban migration crisis in 2015. This article focuses on the factors which contributed to the withdrawal of Costa Rica by looking at: (1) the institutional level of SICA; (2) Costa Rica’s policies that have hindered Central American integration; and (3) Costa Rica’s main reasons for its non-integrationist actions. This article argues that the cause can be found at both the institutional level and the national level. It further shows that SICA failed at deepening its integration due to its supranational ambitions installed in its institutional framework. Moreover, through qualitative research methods, it has been found that Costa Rica’s foreign policy is characterized by defying SICA’s organizational bodies. This article concludes by proposing four major reasons to explain Costa Rica’s non-integrationist actions which can be subsumed under (1) historical aspects, (2) no trade benefits from its membership, (3) immigration issues and lastly, (4) the legitimacy problem of SICA.